Valore dei beni e beni di valore: un contributo sulla valutazione dei beni immobiliari militari - Stefano Stanghellini (Aestimum, 2009)
During the last few years a number of laws have been passed to regulate the way in which surplus military properties (which are no longer operational as defence establishments) are disposed in the open market. A crucial issue of national policy concerns the way in which the value of military properties is calculated. Military properties often have historic, architectural and environmental qualities that favour their use by Local Authorities. This paper will analyse the problem of valuing such property, pointing out the inadequacy of the market value calculation. This paper will discuss how, in the negotiations between the State and the Local Authorities, the focus should be shifted towards cooperation and on exploitation strategies.